Determination of phenol in the Bangsai river water of Bangladesh by gas chromatography-mass spectrometry - M. Amzad Hossain; Farida Yeasmin; S.M. Mizanur Rahman; M.S. Rana; Konica J. Fatema (Химия и технология воды, 2011)
A simple, sensitive and rapid gas chromatography-mass spectrometry (GC-MS) method is proposed for the analysis of some environmentally important highly toxic phenols in water. The concentration level of phenol was determined in water at the sampling stations of Savar, Dhaka Export Processing Zone (DEPZ) and Bank Colony of the Bangsai river, Bangladesh. Water samples were collected from different depth of the sampling stations. The phenolic compounds were extracted with dichloromethane, which was further preconcentrated by evaporation. Different concentrations of toxic phenol were obtained in the river water at the various sampling stations. The concentration of highly toxic phenol was found in the range of 0.01 – 0.998 μg∙L⁻¹. This method could permit the analysis of water for phenol as well as phenolic derivatives with detection limit as low as 100 ng∙L⁻¹.